2020
DOI: 10.1111/hsc.13155
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity, perceived job performance and sense of personal accomplishment among social workers in Israel: The overriding significance of the working alliance

Abstract: Professional identity is one of numerous kinds of identities people can possess throughout their lives, including personal, family, community and workplace identities (Wiles, 2013). Created in the space between individual beliefs and motives, and job-related attributes and experiences, professional identities are considered an important mechanism that affects professionals' attitudes, feelings and behaviours when performing their job (Caza & Creary, 2016). In social work, professional identity is described as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The results of this study showed that professional identity is significantly positively correlated with job performance, which is consistent with previous studies (Levin et al, 2020). Research has shown that nurses with higher professional identity are more likely to demonstrate organisational citizenship behaviour in return (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of this study showed that professional identity is significantly positively correlated with job performance, which is consistent with previous studies (Levin et al, 2020). Research has shown that nurses with higher professional identity are more likely to demonstrate organisational citizenship behaviour in return (Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…No literature was found to report the relationship among nurses' organisational justice, professional identity, emotional labour and job performance. There was some research (Baka, 2018; Levin et al, 2020; Ren et al, 2021) that examined the relationships between perceived organisational justice and job performance, professional identity and job performance and perceived organisational justice and professional identity. The results of this study are consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these subtasks involve a process of building practical knowledge, acquiring skills and adopting a professional attitude. With this, the students then have appropriate knowledge about the professional theories as well as legal frameworks used within the profession, and the ability to estimate, determine and, ultimately, apply these standards to their future professional group (Beijaard, Meijer, & Verloop, 2004;Biesta, 2009;Levin, Roziner, & Savaya, 2020;Rodrigues & Mogarro, 2019;Trede et al, 2012). This third developmental task goes hand in hand with the fourth developmental task (identity change and forming a PI) and begins at the start of the student's study program.…”
mentioning
confidence: 99%